Molecular detection and phylogeny of Hepatozoon ophisauri and Toxoplasma gondii in wild lizards from Khyber Pakhtunkhwa, Pakistan - Ghafar, Sidra; Khan, Asmat Ullah; Khalid, Mustansar; Haq, Sami Ul; Ullah, Saeed; Basit, Umaima; Muqaddas, Hira; Mohammed, Ibrahim Abbas; Mahdi, Ayat Ammar; Khan, Adil; Said, Mourad Ben; Iqbal, Furhan (Folia microbiologica, 2025)
Despite Pakistan's rich reptilian diversity, wild lizards have largely been unexplored for vector-borne parasites. This study reports the prevalence and phylogenetic assessment of Hepatozoon ophisauri and Toxoplasma gondii DNA in the blood samples of 101 wild lizards from Khyber Pakhtunkhwa, Pakistan, captured at altitudes of 1200 to 2250 m above sea level between March 2022 and June 2023. PCR-based molecular analysis identified H. ophisauri DNA in three (3%) lizards of all Laudakia tuberculata. Additionally, 45 (44.5%) lizards tested positive for T. gondii DNA, including L. agrorensis, L. pakistanica, L. tuberculata, and Abblepharus pannonicus. Sequence analysis and BLAST confirmed the presence of H. ophisauri and T. gondii. Phylogenetic analysis showed genetic diversity among the H. ophisauri and T. gondii nucleotide sequences, clustering with reference sequences from reptiles, birds, and ticks. Toxoplasma gondii prevalence varied among species, with the highest rates in L. agrorensis and A. pannonicus (67%), followed by L. pakistanica (45%) and L. tuberculata (43%). This study is the first from Pakistan to report high T. gondii prevalence and low H. ophisauri prevalence in wild lizards. Similar and larger-scale studies in unexplored regions of Pakistan are needed to enhance understanding of these pathogens' genetic diversity and host-parasite interactions.
Keywords: Apicomplexa parasites; Wild lizards; Phylogenetic analysis; PCR; Pakistan